2020
DOI: 10.3168/jds.2020-18541
|View full text |Cite
|
Sign up to set email alerts
|

Antimethanogenic effects of nitrate supplementation in cattle: A meta-analysis

Abstract: Supplementing a diet with nitrate is regarded as an effective and promising methane (CH 4 ) mitigation strategy by competing with methanogens for available hydrogen through its reduction of ammonia in the rumen. Studies have shown major reductions in CH 4 emissions with nitrate supplementation, but with large variation in response. The objective of this study was to quantitatively investigate the effect of dietary nitrate on enteric CH 4 production and yield and evaluate the variables with high potential to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 42 publications
1
12
0
8
Order By: Relevance
“…Several reviews indicate that animal and feed management, diet formulation, and rumen manipulation strategies could significantly decrease enteric CH 4 emissions ( 12 , 16 , 17 ). However, previous studies consisted of qualitative reviews ( 12 ), examined the quantitative effects of a single mitigation strategy ( 18 20 ), or compared CH 4 yield (CH 4 Y; CH 4 per unit of feed intake) between multiple mitigation strategies ( 17 ). Methane yield is only one relevant measure, and other major CH 4 emission and animal performance metrics must be considered to determine the effectiveness and feasibility of mitigation strategies.…”
mentioning
confidence: 99%
“…Several reviews indicate that animal and feed management, diet formulation, and rumen manipulation strategies could significantly decrease enteric CH 4 emissions ( 12 , 16 , 17 ). However, previous studies consisted of qualitative reviews ( 12 ), examined the quantitative effects of a single mitigation strategy ( 18 20 ), or compared CH 4 yield (CH 4 Y; CH 4 per unit of feed intake) between multiple mitigation strategies ( 17 ). Methane yield is only one relevant measure, and other major CH 4 emission and animal performance metrics must be considered to determine the effectiveness and feasibility of mitigation strategies.…”
mentioning
confidence: 99%
“…− has been established as an effective feed additive for mitigating CH 4 emissions in ruminants (Lee and Beauchemin, 2014;Beauchemin et al, 2020;Feng et al, 2020). However, studies aiming to evaluate milk characteristics such as antioxidant capacity and residues of NO 3 − and NO 2 − in response to NO 3 − supplementation are still needed, due to the importance of milk for human consumption.…”
Section: Supplemental Nomentioning
confidence: 99%
“…Nitrate (NO 3 − ) compounds have been explored as feed additives to decrease methane (CH 4 ) production and as dietary NPN sources in ruminants. Recently, Feng et al (2020), using a meta-analytical approach, reported the efficacy of NO 3 − supplementation (mean = 16.7 g/kg of DM) at reducing CH 4 yield (g/DMI) in both dairy cows (15.5 ± 1.15%) and beef cattle (8.95 ± 1.76%). Methane mitigation with NO 3 − occurs because of its role as an alternative metabolic hydrogen ([H]) sink in the rumen, because the reduction from NO 3 − to NH 3 is more thermodynamically favorable than the use of CO 2 to synthesize CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis found similar effects of nitrate on daily CH4 emissions (-15%) 39 . Nitrate has also been shown to decrease daily CH4 emissions and CH4Y in a dose-response manner with no loss of effectiveness over and effectively decreased CH4 over the long-term 40,41 . Similar to 3-NOP, nitrate was more effective in decreasing daily CH4 emissions and CH4Y in dairy than in beef cattle 39 .…”
Section: Dietary Inclusion Of Oil and Fat Decreased Daily Ch4 Emissio...mentioning
confidence: 99%
“…Acclimatization of animals to dietary nitrate is required to avoid methemoglobinemia, but rumen adaptation can be lost within three weeks if nitrate is not continuously fed 43 . Simultaneous sulfate supplementation has been shown to help protect cattle against nitrate toxicity 40 . Nitrate supplementation may increase enteric and possibly manure nitrous oxide emissions 44 .…”
Section: Dietary Inclusion Of Oil and Fat Decreased Daily Ch4 Emissio...mentioning
confidence: 99%